Identification of anti-retinal antibodies in patients with age-related macular degeneration. - Morohoshi, K; Ohbayashi, M; Patel, N; Chong, V; Bird, A; Ono, S (2012)
Age-related macular degeneration (AMD) is the leading cause of irreversible blindness in industrial counties. Recent findings indicate that the autoimmunity is involved in the pathogenesis of the disease. However, there is no autoantibody biomarker applied in a clinical setting for diagnosis and prognosis of AMD. In order to reveal retinal antigens targeted by serum IgG from AMD patients, mouse retinal tissue proteins were separated by 2-dimensional electrophoresis and the proteins in the immunoblots that were specific for dry and wet AMD patients IgG were identified by LC-MS/MS. Retinol-binding protein 3 and aldolase C (ALDOC) were mainly recognized by IgG form wet AMD patients. Pyruvate kinase M2 (PKM2) was targeted by both dry and wet AMD and level of anti-PKM2 IgG antibody was correlated best with the stage of AMD. Expression of ALDOC and PKM2 was decreased in mouse retina from aging whereas PKM2 deposit on RPE was increased in aged mice. Our data demonstrate that sera of AMD patients contain autoantibodies against retinal proteins and anti-PKM2 IgG serves as a biomarker for diagnosis and prognosis of AMD. Further investigation of the association of anti-retinal antibody level with expression level of antigens in retina will be needed to reveal the disease pathogenesis.